2014
DOI: 10.1177/1940161214542954
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of the Debate

Abstract: How do disruptive events such as terrorism, disasters, and crises change public discourses? Do they alter journalistic distinctions between legitimate utterances and unacceptable viewpoints? This article provides answers to these questions through a unique data set concerning the coverage of immigration in Norway before and after the Oslo terror of 2011. The data serve as a natural experiment where we can analyze how immigration discourse was changed with regard to its magnitude, topical emphasis, and the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…The first paper uses panel data, in which the first round ended approximately three months before the attacks on July 22, 2011, and the second round was fielded about a month after the attacks. 19 This panel can be used to examine how prior attitudes determine reactions to attacks, something that is impossible with crosssectional data in which everyone has been "treated" by an attack. In this paper, the panel data are complemented with questions from the second round (after the attacks).…”
Section: Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…The first paper uses panel data, in which the first round ended approximately three months before the attacks on July 22, 2011, and the second round was fielded about a month after the attacks. 19 This panel can be used to examine how prior attitudes determine reactions to attacks, something that is impossible with crosssectional data in which everyone has been "treated" by an attack. In this paper, the panel data are complemented with questions from the second round (after the attacks).…”
Section: Methods and Datamentioning
confidence: 99%
“…Media have a tendency to index the debates in the political elites, and when there is a lack of debate, the media becomes one-sided (Bennett 1990;Entman 2003;Jamieson and Waldman 2003, p. 14;Norris, Kern, and Just 2003, p. 12). The lack of criticism from the opposition may be a consequence of more or less deliberate media gatekeeping, i.e., not allowing critical voices and perspectives to be heard (Figenschou and Beyer 2014;.…”
Section: Framing and Societal Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crises are perceived as disruptive events which are essentially conflicted in nature and thus have the potential to alter journalistic conventions and routines (Figenschou and Beyer 2014;Horsti 2008a), especially if the crises come unexpected and outsider-driven (Nossek 2008). Nacos and Torres-Reyna (2003), for example, found that after the September 11 attacks, US newspaper and television coverage of Muslim-Americans became more balanced, comprehensive and inclusive than before.…”
Section: Frame Variation In Times Of Crisismentioning
confidence: 99%
“…For at store deler av befolkningen skal klare å oppleve at man står sammen og tenker og føler det samme, må splittende forhold midlertidig legges til side. Striden mellom politiske partier, mellom ledere og folk, mellom en kritisk presse og offentlige aktører -alt dette må dempes, slik vi også så i tiden etter 22. juli (Rafoss, 2018a;Figenschou & Beyer, 2014). De få gangene dette skjer, er det mulig å oppleve at felleskap fremstår som ektefølt, autentisk og sant -slik jeg har påvist her.…”
Section: Konklusjonunclassified